Heritability of pain catastrophizing and associations with experimental pain outcomes: a twin study. Issue 3 (March 2015) - Trost, Zina; Strachan, Eric; Sullivan, Michael; Vervoort, Tine; Avery, Ally R.; Afari, Niloofar
Abstract : Abstract: This study used a twin paradigm to examine genetic and environmental contributions to pain catastrophizing and the observed association between pain catastrophizing and cold-pressor task (CPT) outcomes. Male and female monozygotic ( n = 206) and dizygotic twins ( n = 194) from the University of Washington Twin Registry completed a measure of pain catastrophizing and performed a CPT challenge. As expected, pain catastrophizing emerged as a significant predictor of several CPT outcomes, including cold-pressor Immersion Tolerance, Pain Tolerance, and Delayed Pain Rating. The heritability estimate for pain catastrophizing was found to be 37% with the remaining 63% of variance attributable to unique environmental influence. Additionally, the observed associations between pain catastrophizing and CPT outcomes were not found attributable to shared genetics or environmental exposure, which suggests a direct relationship between catastrophizing and experimental pain outcomes. This study is the first to examine the heritability of pain catastrophizing and potential processes by which pain catastrophizing is related to experimental pain response. Abstract : Data from twins were used to examine heritability of pain catastrophizing. Additive genetic factors accounted for 37% of the variance in pain catastrophizing.